1994
DOI: 10.1002/ace.36719946406
|View full text |Cite
|
Sign up to set email alerts
|

Adopting self‐directed learning in continuing professional education: Physicians and architects

Abstract: Various aspects of self‐directed learning have been accepted as a continuing professional education alternative for practitioners of medicine in Canada and of architecture in the United States.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…Schon (as cited in Confessore, 1994) describes this as a "knowing-in-practice." In a study conducted by Sharon Oji looking at adult learning as it applies to TPD, she found that teachers want to problem-solve with their colleagues and learn things that are applicable to practices in their classrooms.…”
Section: Implications For Professional Developmentmentioning
confidence: 99%
“…Schon (as cited in Confessore, 1994) describes this as a "knowing-in-practice." In a study conducted by Sharon Oji looking at adult learning as it applies to TPD, she found that teachers want to problem-solve with their colleagues and learn things that are applicable to practices in their classrooms.…”
Section: Implications For Professional Developmentmentioning
confidence: 99%
“…Thus, one can begin to see the conflicting process and personality characteristic of autonomous learning. Recent research suggests that LA can be viewed as the psychological foundation that leads to the behaviors associated with the process of autonomous learning that includes initiative, resourcefulness, and persistence (Confessore, 1991).…”
Section: Learner Autonomymentioning
confidence: 99%
“…Although recent studies of online education emphasize the importance of the instructor and classmates in such environments, many online courses do not have much student–instructor interaction. Self‐directed learning and training in adult education research is still quite prominent (e.g., Brockett, Stockdale, & Fogerson, 2000; Brookfield, 1984; Confessore & Confessore, 1994; Mezirow, 1981), and some other disciplines have recently begun to integrate this area of study. For example, self‐directed learning in the marketing profession may supplement traditional sales force training and result in increased sales performance (Artis & Harris, 2007).…”
Section: Introductionmentioning
confidence: 99%